Smart Actuators Based on External Stimulus Response - Zheng, Qinchao; Xu, Chenxue; Jiang, Zhenlin; Zhu, Min; Chen, Chen; Fu, Fanfan (Frontiers in Chemistry, 2021)
Smart actuators refer to integrated devices that are composed of smart and artificial materials, and can provide actuation and dampening capabilities in response to single/multi external stimuli (such as light, heat, magnetism, electricity, humidity, and chemical reactions). Due to their capability to dynamically sensing and interact with complex surroundings, smart actuators have attracted increasing attention in different application fields, such as artificial muscles, smart textiles, smart sensors, and soft robots. Among these intelligent material, functional hydrogels with fiber structure is of great value in the manufacture of smart actuators. In this review, we summarized the recent advances in stimuli-responsive actuators based on functional material. We emphasized the important role of functional nano-material-based additives in the preparation of the stimulus response materials, then analyzed the driving response medium, the preparation method, and the performance of different stimuli responses in detail. In addition, some challenges and future prospects of smart actuators are reported.